Vivo [videorecording (Blu-Ray + DVD)] - Miranda, Lin-Manuel, 1980- (Sony Pictures Home Entertainment, 2022)
Vivo, a one-of-a-kind kinkajou, spends his days playing music with his beloved owner Andrés. But when tragedy strikes, it's up to Vivo to deliver a message that Andrés never could: a love letter to his old partner, the famous Marta Sandoval, in the form of a song. Yet in order to get to Marta, who lives a world apart, Vivo will need the help of Gabi, an energetic tween who bounces to the beat of her own offbeat drum, to fulfill his owner's wishes.